Cryogenic safety considerations for Vertical Test Facility for qualifying high-β SRF cavities for the European Spallation Source. (April 2019) - Bizel-Bizellot, L; Pattalwar, S; Pattalwar, N; May, AJ; Wong, P; Liffredo, M
Abstract: A dedicated cryogenic infrastructure has been installed at STFC Daresbury Laboratory to qualify and deliver 84 high-, 0 SRF cavities for the ESS (European Spallation Source) under construction in Lund, Sweden. In order to meet the delivery schedule and optimise the test process efficiently, a large 1.6 m diameter, 3.5 m tall liquid helium cryostat has been developed. RF tests are conducted on 3 cavities at 2 K in one cool-down. There are 3 cryogenic circuits operating at 50 K, 4.2 K and 2 K designed to handle a maximum helium mass flow rates of 4 g/s. Considering the large internal beam pipe and external surface areas of the cavities under test, the pressure relief system has been designed very carefully. Various limiting scenarios and associated safety schemes are presented in detail in this paper.